First year students' boredom in applied communiction skills classroom at a South African university of technology - Erasmus, M.R.; Hall, I. (South African Journal of Higher Education, 2019)
ABSTRACT Researchers worldwide have reported on student boredom in schools as well as in higher education contexts. However, little attention has been paid to this aspect of student response in South Africa’s classrooms. This quantitative study aimed to determine the boredom levels of a group of first-year students at a South African university of technology in the early stages of a compulsory year-long first-year Applied Communication Skills programme conducted in English, and to investigate possible factors associated with boredom. A closed-ended questionnaire was administered to a random sample of 182 students. Unexpectedly, the results revealed lower levels of boredom in class than had been found in earlier international studies. The male students reported less boredom than the female students, and all the students reported significantly less boredom at tertiary level than they had experienced in secondary school. There was no statistically significant correlation between the students’ boredom levels and their home language, or between their boredom levels and their self-reported levels of proficiency in English. Although our study focused just on one subject in a single institution, it suggests that student boredom in South Africa may be less prevalent at tertiary level than previously assumed. Future research could usefully investigate levels of student boredom, and associated factors, across a wider range of classes and higher education institutions.